Informal language stimulation rather than corrective feedback matters in Estonian children's language performance. (October 2019) - Tulviste, Tiia; Tamm, Anni
Abstract: The study examined associations between Estonian children's language performance and their mothers' self-reported language teaching practices, and factors related to the frequency of using these language teaching practices. Mothers reported their language teaching practices, child-rearing value orientation, and their children's expressive vocabulary at 36 months ( N  = 88; M age  = 35.85) via the ECDI-II. Language comprehension and production were directly assessed using the New Reynell Developmental Language Scales (NRDLS). Girls outperformed boys on language production. Children of mothers with university education scored higher than others on all language measures. Mothers with stronger autonomy orientation and fewer children reported more frequent use of informal language stimulation and corrective feedback. Self-reported informal language stimulation was positively related to children's expressive vocabulary and language comprehension, whereas corrective feedback was negatively linked to children's language comprehension and production. This study highlights the importance of engaging language-learning children into conversations rather than explicitly correcting their speech. Highlights: The study identified two different language teaching styles. Mothers' informal language stimulation was positively related to children's language performance. Corrective feedback was negatively related to language performance. Autonomy supportive mothers used both types of language teaching styles more frequently. Mothers with fewer children used both types of language teaching styles less frequently.